Sangiorgi's Report (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
The Review offers in the section “History and Memory” excerpts of the Sangiorgi report. An historical document of inestimable value, as it provides a detailed investigation of the sicilian Mafia and in which, for the first time in history, there is an attempt to demonstrate the organic character of the Mafia.KEYWORDS: Sangiorgi Report, History and Memory, Mafia groups, Protection, Extortion, Corruption